2011
DOI: 10.1007/s11999-011-1892-0
|View full text |Cite
|
Sign up to set email alerts
|

How Reverse Shoulder Arthroplasty Works

Abstract: Background The reverse total shoulder arthroplasty was introduced to treat the rotator cuff-deficient shoulder. Since its introduction, an improved understanding of the biomechanics of rotator cuff deficiency and reverse shoulder arthroplasty has facilitated the development of modern reverse arthroplasty designs. Questions/purposes We review (1) the basic biomechanical challenges associated with the rotator cuffdeficient shoulder; (2) the biomechanical rationale for newer reverse shoulder arthroplasty designs;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 56 publications
0
46
0
1
Order By: Relevance
“…18 However, limited external rotation following this type of RSA has traditionally been a problem and is thought to be due to the medialized COR, which shortens the lever arm of the posterior rotator cuff and also results in a loss of tensioning of the posterior deltoid fibers. 7,20,[22][23][24] A recent cadaveric study by Ackland et al 25 found that the moment arms of most muscles affecting motion of the humerus are significantly altered following RSA, and, in many cases, the posterior deltoid loses its function as an external rotator and becomes an internal rotator, making the integrity of the infraspinatus and teres minor particularly important. The current authors' results indicate that lateralization in RSA may mitigate this to some extent, perhaps allowing the posterior deltoid to function more similarly to the way that it would in a normal shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, limited external rotation following this type of RSA has traditionally been a problem and is thought to be due to the medialized COR, which shortens the lever arm of the posterior rotator cuff and also results in a loss of tensioning of the posterior deltoid fibers. 7,20,[22][23][24] A recent cadaveric study by Ackland et al 25 found that the moment arms of most muscles affecting motion of the humerus are significantly altered following RSA, and, in many cases, the posterior deltoid loses its function as an external rotator and becomes an internal rotator, making the integrity of the infraspinatus and teres minor particularly important. The current authors' results indicate that lateralization in RSA may mitigate this to some extent, perhaps allowing the posterior deltoid to function more similarly to the way that it would in a normal shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, strategies have been developed to limit upper-extremity lengthening in RSA. In cases with a high risk of dislocation, such as revisions or proximal humeral bone loss, use of larger-diameter glenoid components, a superior approach and prosthetic or bony lateralisation of the glenosphere can be considered to avoid excessive tension [71,72]. Nevertheless, if the preoperatively planned lengthening is over four centimetres, the authors recommend using intraoperative nerve monitoring [73].…”
Section: Discussionmentioning
confidence: 99%
“…Reverse total shoulder arthroplasty (RTSA) has been used to treat selected complex shoulder problems as an alternative to standard total shoulder arthroplasty (TSA). (1)(2)(3) However, persistent problems and relatively high complication rates with this procedure are reported to include scapular notching, infection, instability, dislocation, intraoperative fracture, postoperative fracture, brachial plexopathy, and glenoid component loosening. (4)(5)(6) A 5% rate of instability at two years (7) and a 7.5% rate of dislocation at three years (8) indicate that achieving appropriate or optimal soft tissue tensioning during surgery is a major challenge.…”
Section: Introductionmentioning
confidence: 99%
“…(6) The joint center of rotation can be moved to lengthen the humerus and increase stability, (9) but this increases the risks of stress fracture, brachial plexopathy, deltoid overtensioning, and loss of motion. (2) Achieving proper intraoperative soft tissue tension is an obvious surgical goal and surgeons have the ability to choose different implant designs, sizes, placements, and orientations to achieve it. However, methods for measuring soft tissue tension during RTSA have not been reported, and these tension values remain unknown.…”
Section: Introductionmentioning
confidence: 99%